2009
DOI: 10.1088/0004-6256/138/6/1681
|View full text |Cite
|
Sign up to set email alerts
|

The White Dwarfs Within 20 Parsecs of the Sun: Kinematics and Statistics

Abstract: We present the kinematical properties, distribution of spectroscopic subtypes, stellar population subcomponents of the white dwarfs within 20 pc of the sun. We find no convincing evidence of halo white dwarfs in the total 20 pc sample of 129 white dwarfs nor is there convincing evidence of genuine thick disk subcomponent members within 20 parsecs. Virtually the entire 20 pc sample likely belongs to the thin disk. The total DA to non-DA ratio of the 20 pc sample is 1.6, a manifestation of deepening envelope con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 37 publications
(26 reference statements)
6
102
0
Order By: Relevance
“…Of these, only two have T eff below 6600 K (at 6090 and 4660 K). Given that already about half a dozen cool DZ known within 20 pc of the Sun are brighter than this SDSS sample (including van Maanen 2 at only 4.3 pc, Sion et al 2009) this suggests that a large number of cooler DZ remain to be found.…”
Section: Introductionmentioning
confidence: 64%
“…Of these, only two have T eff below 6600 K (at 6090 and 4660 K). Given that already about half a dozen cool DZ known within 20 pc of the Sun are brighter than this SDSS sample (including van Maanen 2 at only 4.3 pc, Sion et al 2009) this suggests that a large number of cooler DZ remain to be found.…”
Section: Introductionmentioning
confidence: 64%
“…14, 16, 17, 18, 22 and 25) must be ruled out as Hyades components, since their updated distances imply residual velocities of more than 20 km s −1 . Indeed, it is obvious that a cluster candidate can not have a residual velocity of the order of the velocity dispersion of field white dwarfs, which is ∼30 km s −1 in each spatial direction (Sion et al 2009). …”
Section: Membership Status Of New Hyades Candidatesmentioning
confidence: 99%
“…The objects are randomly distributed in the galactic X, Y, Z coordinates, with axes pointing to the Galactic centre (X), the direction of galactic rotation (Y), and the North Galactic Pole (Z). The U, V, W velocities are distributed according to a Gaussian weight function using the observed velocity distribution from Sion et al (2009) To derive the mean velocity and the velocity dispersion, Sion et al (2009) assumed zero radial velocity, which, at least, sets a lower limit to the velocity dispersion.…”
Section: Field White Dwarfs Contaminationmentioning
confidence: 99%
“…Searches for such disks around the oldest white dwarfs have been unsuccessful (Kilic et al 2009), but about 15% of local white dwarfs contain metal-rich material in their photosphere, indicative of accretion from a residual dust reservoir (Sion et al 2009). Although these white dwarfs may have a variety of origins, they may include the progeny of the M 2-29-type disks.…”
Section: Evolution Of the Diskmentioning
confidence: 99%